DAMPAK GLOBALISASI TERHADAP TINGKAT LITERASI DIGITAL DI KALANGAN REMAJA PADA MAHASISWA ELEKTRO UNIVERSITAS PENDIDIKAN INDONESIA - Muhammad Asroo Rajib Jajuli; Nashrul Aziz, Muhammad Syahid; Rima Febria Rizkyta (Journal of Education for The Language and Literature of Indonesia, 2024)
This research aims to determine the digital literacy level of Electrical Engineering students from the Indonesian University of Education based on a survey in 2024. A digital questionnaire is used to gather information on technology use, self-assessment of digital literacy, and the challenges faced. The findings show that many students depend on the internet and social media, but have not evenly mastered the concept of digital literacy. Analysis based on youth age reveals that the 18-20 year old group needs intensive training compared to 21-23 year olds. Globalization provides wide access to information but creates challenges in sorting information. Rapid technological developments also require an independent commitment to learning digital literacy. Some of the recommendations include the integration of digital literacy materials into the curriculum, implementation of regular training, interactive online learning, and assistance to vulnerable groups. It is hoped that this research can describe the initial conditions of digital literacy and provide input for appropriate development programs to improve students' digital literacy competencies according to the demands of the current digital era.